2016
DOI: 10.1007/s12010-016-2263-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Four New Distinct ω-Transaminases from Pseudomonas putida NBRC 14164 for Kinetic Resolution of Racemic Amines and Amino Alcohols

Abstract: Four uncharacterized ω-transaminases (ωTAs) from Pseudomonas putida NBRC 14164 have been identified and cloned from the pool of fully sequenced genomes. The genes were functionally expressed in Escherichia coli BL21, and the enzymes were purified and characterized. Four TAs showed highly (S)-selective ωTA activity and converted (S)-α-methylbenzylamine and pyruvate to acetophenone and L-Ala. The maximum activity of cloned enzymes was in the pH range of 8.0-8.5 (Pp36420), 8.5-9.5 (Pp21050), 9.0-9.5 (PpspuC), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…While a number of other discovery approaches have emerged in recent years, such as culture-independent metagenome screening, novel enzymes continue to be discovered in this way ( Fig. 1) (Wilding et al 2015(Wilding et al , 2016Wu et al 2017;Noshahri et al 2019). In the latter example by Noshahri et al, the decades-old approach of using enrichment media with 1-PEA as the sole nitrogen source was given a new lease of life by applying this method to microorganisms from challenging environments.…”
Section: Culture-based Enzyme Discoverymentioning
confidence: 99%
“…While a number of other discovery approaches have emerged in recent years, such as culture-independent metagenome screening, novel enzymes continue to be discovered in this way ( Fig. 1) (Wilding et al 2015(Wilding et al , 2016Wu et al 2017;Noshahri et al 2019). In the latter example by Noshahri et al, the decades-old approach of using enrichment media with 1-PEA as the sole nitrogen source was given a new lease of life by applying this method to microorganisms from challenging environments.…”
Section: Culture-based Enzyme Discoverymentioning
confidence: 99%
“…In contrast to Fold type I ( S )‐selective ω‐TAs, Fold type IV ( R )‐selective ω‐TAs have no reported activity toward β‐ or γ‐amino acids . Enzymes from both superfamilies show activity toward the small‐sized α‐alanine .…”
Section: Discussionmentioning
confidence: 99%
“…Resolution of racemic mixtures has been also achieved through the use of purified enzymes. Wu et al [24] demonstrated that ω-transaminase from P. putida NBRC 14164 entailed high enantioselectivity to different racemic amines and amino alcohols, including α-methylbenzylamine and 2-amino-2-phenylethanol. The enzyme PpspuC achieved ee > 99.0% of (R)-α-methylbenzylamine and (S)-2-amino-2-phenylethanol within 4 h and 24 h respectively, while the removal of racemic α-methylbenzylamine was 50.2% and that of racemic 2-amino-2-phenylethanol reached 50.7%.…”
Section: Biocatalytic Resolution Of Lupanine Enantiomeric Mixturementioning
confidence: 99%